Family Connections: Using Collaborative Partnerships to Support Dissemination. Issue 149 (September 2015) - DePanfilis, Diane
Abstract: Spreading and sustaining evidence‐informed practice in child welfare is complex. In particular, putting in place an active dissemination strategy requires the recognition of these unique challenges. The purpose of this paper is to illustrate how collaborative partnerships between individuals and organizations may represent an opportunity for more widely disseminating evidence‐based practice in child welfare. The benefit of collaborative partnerships has been established as a beneficial mechanism to spread evidence‐supported protocols in medicine and has been experimented with through Breakthrough Series Collaboratives in child welfare. Interagency collaborative teams to lead dissemination of evidence‐informed practice in child welfare are now beginning to be examined as a method to scale‐up practices more quickly. This article will use Family Connections, a multifaceted, community‐based service program that works with families to help them meet the basic needs of their children and prevent child maltreatment as a case study for how collaborative partnerships can aid in dissemination. © 2015 Wiley Periodicals, Inc.